What were the logistics of adaptation production on British television in the 1980s and 1990s, as demonstrated by Granada's "Sherlock Holmes" series (1984-1994)? - Gardner, Denise (2017)
In this thesis I will be examining the logistics of television adaptation, with regard to the Granada series Sherlock Holmes (1984-1994). This series encapsulates many of the major themes in adaptation studies, for example the perception of fidelity, heritage credentials and popularity of ‘classic’ literature. I will consider how budgets, production constraints, scheduling, and changes in the television landscape and audience response impacted on the series over the decade it was on air.